A Comparison of the Diagnostic Accuracy of Common Office Blood Pressure Measurement Protocols. (20th April 2018) - Kronish, Ian M; Edmondson, Donald; Shimbo, Daichi; Shaffer, Jonathan A; Krakoff, Lawrence R; Schwartz, Joseph E
Abstract: BACKGROUND: The optimal approach to measuring office blood pressure (BP) is uncertain. We aimed to compare BP measurement protocols that differed based on numbers of readings within and between visits and by assessment method. METHODS: We enrolled a sample of 707 employees without known hypertension or cardiovascular disease, and obtained 6 standardized BP readings during each of 3 office visits at least 1 week apart, using mercury sphygmomanometer and BpTRU oscillometric devices (18 readings per participant) for a total of 12, 645 readings. We used confirmatory factor analysis to develop a model estimating "true" office BP that could be used to compare the probability of correctly classifying participants' office BP status using differing numbers and types of office BP readings. RESULTS: Averaging 2 systolic BP readings across 2 visits correctly classified participants as having BP below or above the 140 mm Hg threshold at least 95% of the time if the averaged reading was <134 or >149 mm Hg, respectively. Our model demonstrated that more confidence was gained by increasing the number of visits with readings than by increasing the number of readings within a visit. No clinically significant confidence was gained by dropping the first reading vs. averaging all readings, nor by measuring with a manual mercury device vs. with an automated oscillometric device. CONCLUSIONS: Averaging 2 BP readings across 2 office visits appeared to best balance increased confidence in office BP status with efficiency of BP measurement, though the preferred measurement strategy may vary with the clinical context.